AB0026 B-Cell Profile in RA Patients Treated with Two Different Biological Therapeutic Targets: Anti-TNF and Anti-Il6r. A Cross-Sectional Study. (10th June 2014) - Hernández Flόrez, D.; Valor, L.; de la Torre, I.; del Río, T.; Martinez, L.; Naredo, E.; González, C.; Lopez-Longo, J.; Monteagudo, I.; Montoro, M.; Carreño Perez, L.
Abstract : Background: B-cells play a cardinal role in the pathogenesis of rheumatoid arthritis (RA) as demonstrated by the effectiveness of B-cell depletion with rituximab (RTX). In the current cross-sectional study, we assessed the phenotypical changes of B-cell subsets in RA patients treated with different anti-cytokine therapeutic targets, anti-TNF: infliximab (IFX), adalimumab (ADA), etanercept (ETA) and the anti-IL6R: tocilizumab (TCZ) compared to healthy controls (HC). Objectives: To evaluate the changes in the B-cell phenotype in RA patients treated with different biological therapeutic agents. Methods: In this cross-sectional study we assessed B-cells expressing BBR (BAFF binding receptors): BAFF-R, TACI, BCMA and the activation marker CD86 in peripheral blood in a total of 108 patients with RA treated with IFX (n=37), ADA (n=28), ETA (n=28) and TCZ (n=14) as well as in HC (n=19). Clinical status of patients was determined using the 28 joints disease activity score (DAS28), defining non-remission as DAS28≥2.6 and remission as DAS28<2.6. Multiparametric flow cytometry was performed using conjugated monoclonal antibodies directed to CD19, CD27, CD38, IgD, BAFF-R, TACI, BCMA and CD86. Results: We found that the frequency of both naïve (CD19+/CD27-)and memory B-cells (CD19+/CD27+) in all RA treatment groups was similar to HC independently of RA disease activity and treatment. Regarding B-cell subsets, in non-remission patients percentages (%) of transitional B cells were higher in TCZ as compared with HC (p=0.03) while memory resting B cells were higher in ADA compared to HC (p=0.01). In patients in remission % of transitional B cells were also higher in TCZ compared with HC (p=0.001) and it was a difference between patients on TCZ and ADA (p=0.002) while memory resting B cells were also higher in ADA compared to HC (p=0.007). Percentages of naïve B-cells expressing BAFF-R and TACI were similar in all groups, while memory B cells expressing TACI were similar to HC only in remission patients on TCZ. About the BCMA expression on memory B-cells, TCZ was similar to HC in non-remission patients. CD86 expression was higher in non-remission patients on TCZ compared to HC (p<0.0001) and as compared with remission patients on TCZ group (p=0.01). Conclusions: Our findings showed a reduced frequency of memory B-cells expressing TACI and BCMA in patients treated with TCZ which might indicate a possible extra regulatory effect on the B-cell phenotype and therefore on the B-cell survival and maturation process, not yet demostrated using anti-TNF-a therapy. These differences migth be a new marker of success or failure for RA therapy. Disclosure of Interest: D. Hernández Flόrez: None declared, L. Valor: None declared, I. de la Torre: None declared, T. del Río: None declared, L. Martinez: None declared, E. Naredo Grant/research support: UCB and MSD, Consultant for: Abbvie, Roche Farma, Bristol-Myers Squibb, Pfizer, UCB, General Electric Healthcare, and Esaote, C. González: None declared, J. Lopez-Longo: None declared, I. Monteagudo Consultant for: Abbvie, Roche Farma, Bristol-Myers Squibb, Pfizer, UCB, General Electric Healthcare, and Esaote, M. Montoro: None declared, L. Carreño Perez: None declared DOI: 10.1136/annrheumdis-2014-eular.3157